2014
DOI: 10.1002/art.38703
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Trap–Derived Enzymes Oxidize High‐Density Lipoprotein: An Additional Proatherogenic Mechanism in Systemic Lupus Erythematosus

Abstract: Objective Oxidative stress and oxidized high-density lipoprotein (oxHDL) are implicated as risk factors for cardiovascular disease (CVD) in systemic lupus erythematosus (SLE). Yet, how HDL is oxidized and rendered dysfunctional in SLE remains unclear. Neutrophil extracellular traps (NETs), which are elevated in lupus, possess oxidant-generating enzymes including myeloperoxidase (MPO), NADPH oxidase (NOX) and nitric oxide synthase (NOS). We hypothesized that NETs mediate HDL oxidation, impairing cholesterol eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 189 publications
(172 citation statements)
references
References 54 publications
7
163
0
2
Order By: Relevance
“…Indeed, it has been shown that myeloperoxidase, lactoperoxidase, and eosinophil peroxidase have a central role in oxidative damage associated with inflammatory disorders by utilizing hydrogen peroxide and halides/pseudo halides to generate the corresponding hypohalous acid [31]. NETs have been reported to contain oxidative enzymes, including myeloperoxidase, NADPH oxidase, and nitric oxide synthase [32]. Therefore, the inhibitory effect of PDTC on IFN-gamma production by monocytes may be related to both its role as a low molecular weight thiol antioxidant and its potent inhibition of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that myeloperoxidase, lactoperoxidase, and eosinophil peroxidase have a central role in oxidative damage associated with inflammatory disorders by utilizing hydrogen peroxide and halides/pseudo halides to generate the corresponding hypohalous acid [31]. NETs have been reported to contain oxidative enzymes, including myeloperoxidase, NADPH oxidase, and nitric oxide synthase [32]. Therefore, the inhibitory effect of PDTC on IFN-gamma production by monocytes may be related to both its role as a low molecular weight thiol antioxidant and its potent inhibition of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…Human neutrophils and monocytes were isolated by buoyant density centrifugation as described previously (21)(22)(23)(24)(25). The human monocytes were purified by adhesion, cultured in 35-mm plastic dishes (2 3 10 6 cells/dish; BD Biosciences, San Jose, CA), and incubated in 2 mM L-glutamine supplemented RPMI-1640 without phenol red (Life Technology, Carlsbad, CA).…”
Section: Methods Cell Culturementioning
confidence: 99%
“…When HDL becomes oxidised, it loses its cardioprotective effects and displays impaired cholesterol efflux capacity and decreased ability to block low-density lipoprotein (LDL) oxidation 4–10. We recently demonstrated that neutrophil extracellular traps in lupus promote proatherogenic modifications (3-nitrotyrosine and 3-chlorotyrosine oxidation) in HDL and that oxidised lupus HDL displays impaired cholesterol efflux capacity 7. What remains unclear is whether this modified SLE HDL promotes aberrant myeloid cell responses, leading to atherogenesis and systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%